Using the More Than Words Program With Chinese Families: A Case-Control Study - Lok, Jasper S. Y.; Qi, Xin; To, Carol K. S. (Frontiers in Communication, 2021)
This study investigated the effectiveness of the Hanen More Than Words ® (HMTW) program amongst parents of children with autism spectrum disorder (ASD) in Hong Kong. In this prospective cohort study, 31 Cantonese-speaking young children with ASD and their parents were divided into either the HMTW group (n = 26) or a control group (n = 5). The HMTW intervention was provided over 11 weeks. The children’s communication abilities were measured prior to the intervention (Time 1) and one month after the end of the intervention (Time 2), and the results were compared between the two groups. The parents’ attributes and demographic information were measured at Time 1. The results showed a significant increase in children’s communication and social skills in the HMTW group compared with the control group. Children of parents with lower levels of Time 1 parenting self-efficacy exhibited facilitated growth in communication and social skills. These findings provide evidence of the effectiveness of the HMTW program in a Chinese cultural setting and demonstrate an important link between parenting self-efficacy and the effectiveness of the HMTW program.